Hubungan Aktivitas Fisik dengan Kejadian Dismenore Primer pada Remaja Putri di SMP Negeri 5 Kota Langsa - Nurhayati Nurhayati; Irma Hartati; Mailisna Mailisna (CV. KAMPUS AKADEMIK PUBLISING, 2026)
According to the World Health Organization (WHO), the incidence of dysmenorrhea is quite high worldwide. The average incidence of dysmenorrhea in young women is between 16.8-81%. The prevalence of dysmenorrhea in Indonesia is 64%, consisting of 54.89% primary dysmenorrhea and 9.36% secondary dysmenorrhea. One effective way to prevent dysmenorrhea is by doing physical activity such as exercise. This study was conducted to determine the relationship between physical activity and the incidence of primary dysmenorrhea in adolescent girls at SMP Negeri 5 Langsa City. This study is an analytic study with a cross-sectional nature. The population in this study were all adolescent girls at SMP Negeri 5 Langsa 186, the number of samples was 65 samples with the sampling technique carried out by Proportional Stratified Random Sampling. Data analysis was carried out using univariate and bivariate analysis using the Chi-Square test. The results showed that of the 65 respondents, the majority (37 respondents) had low levels of physical activity. The results of the study showed that the incidence of dysmenorrhea in adolescent girls was mostly moderate (26 respondents (40%), and the physical activity of adolescent girls was mostly in the low category (40 respondents (61.5%). There was a relationship between physical activity and the incidence of dysmenorrhea in adolescent girls with a p-value of 0.000 (p<0.05). The results of this study can be used as a policymaker to increase activities that can increase physical activity in adolescents by increasing extracurricular hours and educating adolescent girls about the importance of physical activity in reducing primary dysmenorrhea.